Recycling of RAP (Reclaimed Asphalt Pavement) as aggregate for structural concrete: experimental study on physical and mechanical properties - Nicoletta Russo; Andrea Filippi; Maddalena Carsana; Federica Lollini; Elena Redaelli (Discover Civil Engineering, 2024)
Abstract The replacement of natural aggregate in concrete with artificial and/or recycled one has recently gained attention as meaningful strategy to reduce the environmental impact of structural concrete and promote circular economy principles. This study investigated the possibility to use Reclaimed Asphalt Pavement (RAP), in the “as received conditions”, as a partial or complete substitution of natural aggregate for structural concrete. RAP aggregate was firstly characterized in terms of grain size distribution, density, assessment of fines, chloride content, moisture content and water absorption. Subsequently, a total of twenty-four concrete mixes were designed, considering two cement types, two w/c ratios and several aggregate substitution percentages. For each mix, properties at the fresh and hardened state were investigated, such as workability, density and total open porosity, compressive strength, dynamic modulus of elasticity, and electrical resistivity. Results showed that RAP has a good potential to be used in reinforced concrete, provided that different water absorption and moisture content are considered in the mix design. RAP concrete was characterized by a lower density and increased total open porosity; however, an accurate tailoring of the concrete recipe could compensate the strength loss for several applications. Other properties, such as electrical resistivity and the relationship between dynamic modulus of elasticity and compressive strength did not result significantly altered by the presence of RAP.